UV Induced Biosynthesis of Cyano-sunscreen “Scytonemin” by Leptolyngbya mycodia and its Effectual Antioxidant Activity: Scytonemin Production in Cyanobacterium Leptolyngbya mycodia - Gelareh Sheibani Madrahi; Fereshteh Naeimpoor (Iranian Journal of Pharmaceutical Sciences, 2022)
The indole-alkaloid scytonemin, an ecologically and pharmaceutically important secondary metabolite, is exclusively biosynthesized by some cyanobacteria. Due to its photoprotective function and valuable antioxidant capacity, this cyano-sunscreen may be of great value for production of natural sunscreen in cosmetic and other pharmaceutical industries. As scytonemin is only produced by some cyanobacterial species, identification of novel strains and verification of synthesis induction factors are important research areas. In the present study, using the high-performance liquid chromatography and mass spectrometry analyses, scytonemin was characterized (UVλmax ) at 370 nm; m/z 545) in two filamentous cyanobacteria: Leptolyngbya mycodia and Phormidium sp. Under photosynthetic active radiation (PAR), L. mycodia revealed superior growth as well as scytonemin specific content of 0.0427 (Aλ/mg d.w.). As one of the physicochemical stressors on regulation of scytonemin biosynthesis, the role of UV irradiation in synthesis induction was examined. A remarkable change was observed on scytonemin specific content under PUAB regime (280-700 nm) compared to PAR (400–700 nm). UV-B (280–315 nm) significantly induced scytonemin synthesis up to 4.25 Aλ /mg d.w. while synthesis (2.31 Aλ/mg d.w.) to a lesser extent was observed under UV-A (315-400 nm). Moreover, present study confirmed the role of extracted scytonemin as an active antioxidant, indicating its strong radical scavenging (IC50=48.84%) with relatively high (61%) antioxidant rate at concentration of 200 μg/l. This is the first report on the UV-induced scytonemin biosynthesis by cyanobacterium L. mycodia and its remarkable antioxidant activity is of great value for future biotechnological research and development of natural sunscreens.